Smart Intermediation: The Role of Systemic Intermediation for Advancing Sustainability by Smart Grid Demonstration Projects - Leeb,Antonia Katharina (IIIEE Master Thesis, 2025)
Electricity grids are essential to industrialized societies, yet they are increasingly unable to meet the dual demands of increased electrification and electricity system decarbonization. Smart grids offer a solution to these challenges by integrating information and communication technologies into the physical grid. However, despite their potential, smart grid implementations often fail to deliver the expected benefits. These implementations are largely project-based, with publicly funded, large-scale demonstration projects playing a particularly important role. In order to fulfill their potential, smart grids must not only be technically feasible but also reflect social and institutional requirements. This thesis takes a socio-technical approach, investigating how systemic, transition-focused intermediation can advance the contribution of large-scale smart grid demonstration projects to the broader energy sector transition. The investigation is based on an in-depth qualitative case study on the German large-scale smart grid project C/sells. A novel theoretical framework relating intermediary functions and actors across three levels of systemic intermediation is developed, allowing for a comprehensive analysis of the project’s ecology of intermediaries. Empirically, the study finds that systemic, transition-focused intermediation can provide a suitable governance mode for advancing sustainability by smart grid demonstration projects. Intermediation created networks, visions, and institutional space for project initiation, promoted internal directionality, learning, and community building, enabling project implementation. Importantly, intermediation connected the project to the broader energy system transformation by creating stable networks, articulating visions, needs, and expectations towards relevant institutional forums, and supporting learning, replication, and upscaling. Unique characteristics of intermediation in the project context were identified. These include the institutionalization of intermediation within the project structure and the role of intermediary ‘architects’ in developing the intermediary ecology. Finally, the limitations of project-level intermediation indicate a persisting need for system-level intermediary ecologies. Conceptually, the study highlights the value of intermediation concepts for understanding how projects can drive sustainability transitions.
Keywords: smart grids; demonstration project; energy transition; socio-technical system; sustainability by projects